Is Expanded HIV Testing Associated with Earlier HIV Diagnosis? Results from an HIV Clinic in Guatemala City. (May 2016) - Liggett, Alisha; Medina, Narda; Samayoa, Blanca; Mercado, Danicela; Castillo, Mirna; Argueta, Erwin; Anderson, Miguel; Anderson, Matthew; Arathoon, Eduardo
Background: Most patients in Guatemala are diagnosed with advanced HIV disease. Patients that present late in the disease process may miss the morbidity and mortality benefits associated with early treatment and may unknowingly spread HIV to others. Research Questions: We examined trends in HIV detection and levels of immunosuppression at diagnosis from 2005 -2012 to determine if expanded HIV testing was associated with earlier detection of HIV. Setting: This study was conducted at the Clínica Familiar Luis Ángel García (CFLAG), a major HIV center associated with one of Guatemala's two national hospitals. HIV testing expanded rapidly after 2007 due to grants from the Global Fund which allowed for routine prenatal testing. Methods: This study examined existing hospital and clinic databases from to evaluate results from HIV tests performed, and baseline CD4 cells/mm 3 on all patients newly diagnosed with HIV infection from 2005 to 2012. Results: We found a decline in the number of HIV positive tests over the study period despite an increase in the total number of tests performed. Sixty-two percent of HIV infected individuals had AIDS at diagnosis. We observed a decrease in median CD4 cells/mm 3 among the prenatal testees and no change in non-prenatal testees. Discussion: Expanded HIV counseling and testing services in our clinic did not result in earlier HIV diagnosis.